2020
DOI: 10.1177/1120672120932833
|View full text |Cite
|
Sign up to set email alerts
|

Total or subtotal full thickness recipient bed cut to repair donor–recipient curvature disparity in cases of DM rupture with manual DALK

Abstract: Purpose: To report how to manage a specific type of Descemet’s membrane (DM) rupture during manual DALK with a concurrent donor–recipient disparity of curvature. Methods: Case report of two patients that had DM rupture during manual DALK with a concurrent donor–recipient disparity of curvature; the recipient bed was flatter (post-infectious scar, case 1) and steeper (keratoglobus, case 2) than the donor. Preoperative diagnosis, clinical exam, and best spectacle correct visual acuity (BSCVA) have been reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Its indications have broadened to include not only routine keratoconus, post-infectious leukoma, and stromal dystrophies, but also serious infective keratitis refractory to medical treatment, keratoconic eyes with history of previous hydrops, descemetocele, and keratoglobus. 5,[9][10][11][12][13][14] Several studies report good outcomes of DALK performed in eyes affected by keratoconus with history of corneal hydrops, demonstrating that the presence of a break into the DM is not an absolute contraindication for DALK. 9 Additionally, it has been also demonstrated that intraoperative unexpected DM ruptures may be mended with good results.…”
Section: Discussionmentioning
confidence: 99%
“…Its indications have broadened to include not only routine keratoconus, post-infectious leukoma, and stromal dystrophies, but also serious infective keratitis refractory to medical treatment, keratoconic eyes with history of previous hydrops, descemetocele, and keratoglobus. 5,[9][10][11][12][13][14] Several studies report good outcomes of DALK performed in eyes affected by keratoconus with history of corneal hydrops, demonstrating that the presence of a break into the DM is not an absolute contraindication for DALK. 9 Additionally, it has been also demonstrated that intraoperative unexpected DM ruptures may be mended with good results.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to use a 0.25-mm oversized donor might have played some role too. 8 This kind of double AC, refractory to rebubbling, can be solved by using our technique of anchoring sutures.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to use a 0.25-mm oversized donor might have played some role too. 8 This kind of double AC, refractory to rebubbling, can be solved by using our technique of anchoring sutures. It is known that the recovery from persistent corneal edema due to second anterior chamber formation is a prolonged process.…”
Section: Discussionmentioning
confidence: 99%
“…Significant disparity of curvature between donor and recipient can lead to a persistent double anterior chamber and may necessitate surgical repair. 4,14,16 Two different types of disparity can occur; the recipient bed can be significantly flatter (Fig. 3A) or steeper (Figs.…”
Section: Management Of Particular Dm Ruptures In Dalk Casesmentioning
confidence: 99%
“…These specific surgical techniques have previously been described in detail and published by our group. 4,14,16 Management of Uncommon DM Rupture Cases DM breaks occurring while inserting the needle or cannula into the stroma looking for a deep plane to inject air and attempt a BB (1 case) were managed by switching to a manual DALK without trying to attempt a pneumatic or viscodissection. At the end of the surgery, an air bubble was left in the AC.…”
Section: Management Of Particular Dm Ruptures In Dalk Casesmentioning
confidence: 99%